Analisis Survival dengan Menggunakan Metode Kaplan Meier pada Penderita Penyakit Demam Berdarah Dengue (DBD) - Adnan Sauddin; M Ichsan Nawawi; Muhalki Muhalki (Poltekkes Kemenkes Padang, 2021)
The Kaplan Meier method is one of the methods in survival analysis that is used to find out how big the chances of survival of a person suffering from a certain disease. The Kaplan Meier method calculates the patient's life by providing a definite survival proportion. The purpose of this study was to determine the relationship between age and length of treatment and patient status. The life chances of DHF patients using the Kaplan Meier method at the Lasinrang District Hospital. Pinrang. The results showed that there was no relationship between age and length of treatment as well as the status of DHF patients in Lasinrang Hospital Kab. Pinrang. The conclusion of this study is that the chance of survival of DHF patients before a patient dies is 100%. However, the chance of patient survival after 1 patient died during the observation was 99.1%. It is recommended that clinical monitoring should always be carried out, to predict the correct diagnosis of Dengue Virus Infection. And sero-epidemiological studies should continue to be carried out in many island capitals in Indonesia.